Mapping the Bekasi City KPAD Communication Strategy to Optimize the Role in the Prevention, Disclosure and Assistance of Violence against Children, Especially during the COVID-19 Pandemic - Novrian Novrian; Ira Dwi Rachmani; Suparman Suparman (Budapest International Research and Critics University, 2022)
The Indonesian Child Protection Commission as the implementer of the mandate of the child protection law has the responsibility for the sustainability of child protection throughout Indonesia involving all stakeholders, especially institutions under the government, to strengthen the duties and functions of KPAI in terms of supervision and assistance in child protection. Establishing a Regional Child Protection Commission, abbreviated as KPAD, which is stated in Article 74 paragraph (2) states that the regional government in this case is needed to form a Regional Child Protection Commission or similar institution. With the establishment of the KPAD, it is hoped that the work of protecting children at the regional level can be maximized. The Bekasi City KPAD is present based on statutory orders and is determined through the appointment of the Bekasi Mayor Decree and the presence of the Bekasi City KPAD is expected to be a strengthening of advocacy work in this case the protection of children where the function of the KPAD based on the law has the function of supervision and assistance to work -The work of institutions related to child protection, besides that, the task of mentoring is also an important role of the Bekasi City KPAD. The problem of this research is how the Bekasi City KPAD Communication Strategy Formulation for Stakeholders in Efforts to Handle Violence against Children in Bekasi City during the Covid-19 Pandemic 19? The method of writing this paper uses desk research, data and information obtained from information sources in the form of observations, interviews, literature, journals, e-books, media reports and other sources obtained from online media during the period March 2019 to October 2021. Results the purpose of this research is to find out the Mapping Strategy used by KPAD in dealing with various problems in the protection of children in the city of Bekasi, both prevention and in handling cases that occur.